Pathogenicity of memory Th2 cells is linked to stage of allergic rhinitis. Issue 2 (12th September 2017) - Iinuma, T.; Okamoto, Y.; Morimoto, Y.; Arai, T.; Sakurai, T.; Yonekura, S.; Sakurai, D.; Hirahara, K.; Nakayama, T.
Abstract: Background: Allergic rhinitis (AR) consists of three developmental stages that are based on the presence/absence of antigen‐specific IgE and symptoms. The pathogenic Th2 (Tpath2) cells constitute a population of Th2 cells with additional potentially pathogenic characteristics. We examined the relationship between Tpath2 cells and the stages of allergic rhinitis by focusing on ST2, which is an IL‐33 receptor. Methods: Patients with Japanese cedar pollen‐induced AR (JCP‐AR) and healthy volunteers were divided into "nonsensitized, " "asymptomatic sensitized (AS), " and "JCP‐AR" groups. We analyzed the ST2 expression and the Th2 function of cultured CD4 + T cells. Next, we observed the progress of patients in the AS stage around the time of seasonal pollen dispersal, with the characteristics of Th2 cells. Results: The ST2 expression of T cells was only upregulated in the AR group. The production of IL‐4 and IL‐13 was found in CD4 + T cells obtained from AS by stimulation with JCP, but reactivity to IL‐33 was not observed. Although IL‐33 did not induce the elevation of IL‐4 production in the JCP‐AR group, IL‐33 substantially increased the production of IL‐5 and IL‐13 in comparison with antigen stimulation alone. In newly afflicted patients, the increased expression of ST2 and elevated reactivity to IL‐33 was observed, even before the pollen dispersal season. Conclusions: Our study demonstrated that the pathogenicity of memory Th2 cells is linked to sensitization and the stage of allergic rhinitis. Therefore, Tpath2 cells may provide useful insights into the mechanism of the onset and progression of allergic rhinitis.